2016
DOI: 10.1007/s10689-015-9854-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an interventional counselling procedure in families with a BRCA1/2 gene mutation: efficacy and safety

Abstract: Background: Predictive genetic testing has high impact on cancer prevention for BRCA carriers and passing this information in BRCA families is important. Mostly, this is proband-mediated but this path is defective and denies relatives lifesaving information. Objective: To assess the efficacy/safety of an intervention, in which relatives are actively informed. Design: Sequential prospective study in new BRCA families. The proband informed relatives about predictive testing (phase I). After 6 months, a letter wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 23 publications
(29 reference statements)
0
67
2
Order By: Relevance
“…Other research has shown benefits from direct contact with at-risk relatives 30. Studies involving a range of illnesses (eg, BRCA1/2 , Lynch, Cowden syndrome) have shown that when GHP-mediated contact, uptake of testing was greater among at-risk relatives compared with when contact was patient-mediated 15 31. A Western Australian study adopted a cascade screening process derived from an Australasian model of care for familial hypercholesterolaemia in accordance to local and national guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown benefits from direct contact with at-risk relatives 30. Studies involving a range of illnesses (eg, BRCA1/2 , Lynch, Cowden syndrome) have shown that when GHP-mediated contact, uptake of testing was greater among at-risk relatives compared with when contact was patient-mediated 15 31. A Western Australian study adopted a cascade screening process derived from an Australasian model of care for familial hypercholesterolaemia in accordance to local and national guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting the acceptance of more direct approaches in practice, the authors of an international review found there was a clear focus on uninformed relatives and an endorsement of proactive approaches to encourage dissemination among family members in practice guidelines and position papers (Forrest et al 2007). Despite two studies establishing that writing directly to at-risk family members nearly doubles the amount of relatives presenting to the genetics service to clarify their risk (Sermijn et al 2016;Suthers et al 2006), outside of research settings, the direct contact of at-risk relatives is not currently feasible in genetic counseling practice.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding of limited family communication about indeterminate negative BRCA test results is similar to findings in studies of BRCA‐positive families. Indeed, even when genetic counselors undertake interventions to help counselees notify family members, a large portion of potentially BRCA‐positive family members remain uninformed (Mendes, Paneque, Sousa, Clarke, & Sequeiros, ; Sermijn et al, ; Suthers, Armstrong, McCormack, & Trott, ).…”
Section: Discussionmentioning
confidence: 99%